A marginal Jew ; v. 1 rethinking the historical Jesus - Meier, John P. (New York, NY Doubleday, 1991)
Contents : v. 1 : The roots of the problem and the person. Includes bibliographical references, indexes, maps and charts.
Keywords: Christology